RESOLUSI KONFLIK SOSIAL MELALUI PENDEKATAN KOMUNIKASI DI LINGKUNGAN MONJOK DAN KARANG TALIWANG KOTA MATARAM - Siti Nurul Yaqinah (Jurnal Mediakita : Jurnal Komunikasi dan Penyiaran Islam, 2019)
The conflict is one of the phenomena that occurs as part of the dynamics of the community. Among the social conflictthatrooted strongly in the community ofthe city ofMataramwasthe conflictMonjok andKarangTaliwang. Therefore, this research aims to know the background of the occurrence of social conflict, the impact of conflict on the lives of communities and communications in an effort to approach conflict resolution in an environment of Monjok and Karang Taliwang. This research uses a qualitative descriptive method, data obtained through interviews, observation and documentation. The analysis used was the reduction of the data, the presentation of data, and the withdrawal of the conclusion. To test the validity of the data, the researchers conducting the study, extra time triangulation of methods and sources, and the associated examination. The results obtained in this study are a conflict that occurs between the citizens of Monjok and Karang Taliwang triggered by the removal of the trash container by Karang Taliwang minimal coordination and dissemination so as to trigger the action of the destruction caused by the citizens Monjok. Another trigger is a young man’s dispute and the existence of a third party that provokes the situation for transferability. So, the impact on the conflict; psychological society, communication, economic impact and stalled social impact. Therefore, some approaches used in handling the conflict approach is communication through Consolas, the communication approach through negotiations or deliberations, approach to communication through mediation and communication approaches involving stakeholders.